Transforming Oral Literature into Educational Media: Integrating Character Values in Indonesian Language Learning - Erni, Erni; Piliang, Wilda Srihastuty Handayani; Ulya, Ridha Hasnul; Fatmadona, Rika (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to identify character values embedded in the folktales of Pelalawan and to design a locally grounded instructional model to strengthen students’ character education. A descriptive qualitative approach was employed. The researchers analyzed two folktales, “The Golden Chain from the Riverbed” and “The Tale of the Sacred Ketobong” collected through documentary sources. Interactive content analysis was used as the analytical technique. Findings reveal character values such as simplicity, sincerity, humility, responsibility, and adherence to moral norms. The study concludes that folktales hold significant potential as effective educational media in Indonesian language and literature instruction, offering a contextual approach to character formation among students.